Aggregate skewness and the business cycle - Martin Iseringhausen; Ivan Petrella; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2021)
We develop a data-rich measure of expected macroeconomic skewness in the US economy. Expected macroeconomic skewness is strongly procyclical, mainly reflects the cyclicality in the skewness of real variables, is highly correlated with the cross-sectional skewness of firm-level employment growth, and is distinct from financial market skewness. Revisions in expected skewness deliver dynamics that are nearly indistinguishable from those produced by the main business cycle shock of Angeletos et al. (2020). This result is robust to controlling for macroeconomic volatility and uncertainty, and alternative macroeconomic shocks. Our findings highlight the importance of higher-order dynamics for business cycle theories.
Keywords: C22; C38; E32; 330; Asymmetry; principal component analysis; quantile regression; VAR